C7-T1 Anterior Closing Wedge Bone-Disc-Bone Osteotomy for the Treatment of Cervical Hyperlordosis in Muscular Dystrophy A New Technique for Correction of a Rare Deformity - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2014)
Study Design. A new surgical technique of cervical closing wedge osteotomy to correct an extension deformity of the cervical spine in patients with muscular dystrophy presenting clinically with debilitating hyperlordosis is described, and 3 cases are reported. Objective. To describe a new surgical technique with emphasis on the clinical results and the effect of osteotomy on sagittal balance, gaze angle, and spinopelvic parameters. Summary of Background Data. Previous reports of cervical osteotomy essentially have described opening wedge (extension osteotomy) for correction of severe flexion deformities. To the authors' knowledge, C7-T1 closing wedge osteotomy to correct hyperextension deformity due to muscular dystrophy in the cervical spine has not been described previously. Methods. Three male patients aged 16, 16, and 21 years presented with cervical hyperlordosis due to Becker muscular dystrophy. There was upward deviation of forward gaze in all patients. Anterior closing wedge (bone-disc-bone) osteotomy of C7-T1 was performed followed with a posterior release correction and instrumented stabilization. The chin-brow angle was visualized with the aid of fluoroscopy during the operation. After closure and posterior fixation, patient was turned supine again and the osteotomy site was grafted and fixed with a plate to further strengthen the construct and to prevent any translation. Results. The gaze angles and both sitting and standing postures of the patients markedly improved. There was documented fusion at the osteotomy sites. The patients were free of complaints at the last follow-up. Conclusion. Bone-disc-bone closing wedge osteotomy done at C7-T1 level is a technically demanding procedure but results in significant acute clinical and radiological improvement in patients with hyperextension deformity of the cervical spine.
Keywords: muscular dystrophy; cervical spine; hyperextension; hyperlordosis; bone disc bone osteotomy; C7-T1 osteotomy; SPINE; KYPHOSIS